COGNITIVE BEHAVIOR THERAPY UNTUK MENURUNKAN PERILAKU MENGHINDAR - Muhammad Nur Hidayah (Al-ATHFAL: Jurnal Pendidikan Anak, 2020)
13-year-old subject that is experiencing the avoidance behavior problem. The assessment method is carried out on the subject of observation, interviews, graphic tests, and standard prgressive matrices (SPM) intelligence tests. A given intervention is using the cognitive Behavior Therapy (CBT) approach with cognitive restructuring techniques, respiratory relaxation, and 8-session exposure. The goal of this intervention is to lower the avoidance behavior of chickens. The result of this intervention is that the subject is no longer dodge to the chickens and can interact directly with the chickens by holding and carrying it. It does not release because of the strong desire of the subject not to shy away from dealing with chickens and the support of parents and class guardians in school.